Shifting Punishment on Minorities: Experimental Evidence of Scapegoating - Michal Bauer; Jana Cahlíková; Julie Chytilová; Gerald Roland (Institute of Labor Economics (IZA), 2021)
This paper provides experimental evidence showing that members of a majority group systematically shift punishment on innocent members of an ethnic minority. We develop a new incentivized task, the Punishing the Scapegoat Game, to measure how injustice affecting a member of one's own group shapes punishment of an unrelated bystander ("a scapegoat"). We manipulate the ethnic identity of the scapegoats and study interactions between the majority group and the Roma minority in Slovakia. We find that when no harm is done, there is no evidence of discrimination against the ethnic minority. In contrast, when a member of one's own group is harmed, the punishment "passed" on innocent individuals more than doubles when they are from the minority, as compared to when they are from the dominant group. These results illuminate how individualized tensions can be transformed into a group conflict, dragging minorities into conflicts in a way that is completely unrelated to their behavior.
Keywords: C93; D74; D91; J15; 330; punishment; minority groups; inter-group conflict; discrimination; scapegoating; lab-in-field experiments